Analytical Methods For The Identification And Conformation Of The Principal Cannabinoid Metabolite In Urine. - Rajananda, V.; Navaratnam, Profesor Madya (Dr.) V.; Nair, N.K. (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1985)
Cannabis is obtained from the flowering tops and dried leaves of the hemp plant CANNABIS SATIVA L, in particular from the resin produced by the flowering tops. Many preparations of the drug are in common use, varying in potency.